Transformation of Acinetobacter sp. Strain BD413(pFG4ΔnptII) with Transgenic Plant DNA in Soil Microcosms and Effects of Kanamycin on Selection of Transformants - Nielsen, Kaare M. (American Society for Microbiology, 2000)
Here we show that horizontal transfer of DNA, extracted from transgenic sugar beets, to bacteria, based on homologous recombination, can occur in soil. Restoration of a 317-bp-deleted nptII gene in Acinetobacter sp. strain BD413(pFG4) cells incubated in sterile soil microcosms was detected after addition of nutrients and transgenic plant DNA encoding a functional nptII gene conferring bacterial kanamycin resistance. Selective effects of the addition of kanamycin on the population dynamics of Acinetobacter sp. cells in soil were found, and high concentrations of kanamycin reduced the CFU of Acinetobacter sp. cells from 10(9) CFU/g of soil to below detection. In contrast to a chromosomal nptII-encoded kanamycin resistance, the pFG4-generated resistance was found to be unstable over a 31-day incubation period in vitro.